2015
DOI: 10.1167/iovs.15-16924
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Caspase-12 to Preserve Vision in Mice With Inherited Retinal Degeneration

Abstract: PURPOSE. The unfolded protein response is known to contribute to the inherited retinal pathology observed in T17M rhodopsin (T17M) mice. Recently it has been demonstrated that the endoplasmic reticulum stress-associated caspase-12 is activated during progression of retinal degeneration in different animal models. Therefore, we wanted to explore the role of caspase-12 in the mechanism of retinopathy in T17M mice and determine if inhibiting apoptosis in this way is a viable approach for halting retinal degenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…In support of this hypothesis, the UPR reduction due to knockdown of ATF4 in T17M mice correlates with normal levels of activated caspase-3/7 at P30. Perhaps, similar to targeting caspase-7 [ 1 ] and 12 [ 48 ], this approach is sufficient to delay vision loss in T17M mice.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, the UPR reduction due to knockdown of ATF4 in T17M mice correlates with normal levels of activated caspase-3/7 at P30. Perhaps, similar to targeting caspase-7 [ 1 ] and 12 [ 48 ], this approach is sufficient to delay vision loss in T17M mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact role PERK plays in the retina has not been carefully assessed because detecting phosphorylated PERK (p-PERK) in vivo has proven challenging with current methodology. Although p-PERK has not been detected in the retinas of mice with retinal degenration (RD), the activation of the UPR and ISR has been observed 3 , 10 , 11 . Interestingly, a recent study showed a 50% decrease in p-eIF2α in P23H rats following treatment with a PERK inhibitor 3 , but the correlation between the ISR and translation has not been explored in RD.…”
Section: Introductionmentioning
confidence: 99%
“…The pathological mechanisms involved in rod photoreceptor cell death in degenerating retinas include, but are not limited to, activation of the Unfolded Protein Response (UPR) [46], inflammatory signaling [4,79], and oxidative stress, [10,11] eventually resulting in both apoptotic and non-apoptotic cell death [1215]. Expression of human mutant T17M rhodopsin (T17M) in mouse rods results in severe retinal degeneration that mimics human adRP.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of human mutant T17M rhodopsin (T17M) in mouse rods results in severe retinal degeneration that mimics human adRP. The UPR or ER stress response is activated beginning at postnatal day 15 (P15) [16] and is involved in retinal degeneration in these mice [4], together with calpain-activated pathway [15,17] and inflammation [4]. Recent studies have highlighted the activation of microglia in the RP retina preceding photoreceptor cell death.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation